Fenomena Rendahnya Minat Menguasai Keterampilan Membaca serta Solusinya dari Sudut Pandang Siswa dan Guru - Mukhlis Utsman; Muh Sabilar Rosyad (Jurnal Pendidikan Bahasa Arab, 2023)
The skill of reading Arabic texts the pesantren environment is something that is necessary for students to master. The superiority of a strategy or methodology used in studying it must be in line with the self-motivation of everyone. Therefore, harmony between strong tendencies and the advantages contained in a method is deemed necessary to improve reading skills. This research aims to: 1) Reveal the reality of low motivation and the tendency of students to improve Maharah Qira'ah; 2) Offering a problem-based idea to make Maharah Qira'ah learning successful. This study uses a phenomenological study with a qualitative approach. As for researchers as the main instrument, they directly participate in collecting data sourced from students, teachers, and policy makers at Islamic boarding schools, all of which are obtained through interviews, observation, and documentation. Furthermore, the data was analyzed using interactive descriptive analysis techniques. The findings in this study are 1) The low motivation of students in learning Maharah Qira'ah is influenced by several external and internal factors simultaneously; 2) Some of these problem-based ideas include: providing the right books, working with alumni stakeholders, building an interesting and fun atmosphere, and sharing with other students.